(untitled) (Research, Society and Development, 2021)
The emergency contraceptive was developed for emergency use in order to avoid pregnancy, its mechanism of action prevents fertilization, has no abortive effect and its improper use can cause health risks. With emphasis on the population of the periphery of São Paulo belonging to the neighborhoods Cohab Raposo Tavares and Vila Élida, the field research investigated the knowledge about the method, with the participation of 26 volunteers aged between 19– 47 years, men’s and women’s, at the time of dispensation. The main reason for using the method was unprotected sexual intercourse, with 88.8% of the women and 87.5% of the men. The incidence of use was higher than the compared studies, three times or more after initiating sexual intercourse. It was observed that the most sought means for indicating the method was pharmaceutical orientation (33.3% of women and 75% of men). Knowledge about the morning-after pill among the volunteers is discrepant and scarce. Most of the interviewees reported no significant adverse reactions, however the predominant symptom was nausea (42.85%). Appointments with a gynecologist are important for family planning and for choosing a contraceptive method. 61% of the women informed that they often go to the doctor, while 28% justify not going to the doctor due to lack of time, shame, difficulty in scheduling due to the pandemic, lack of access to health care, and lack of interest. The presence of the pharmacist in promoting the proper use together with basic sex education are essential for the dissemination of correct information.